2020
DOI: 10.1136/jech-2020-215060
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and health behaviours before and during the initial phase of the COVID-19 lockdown: longitudinal analyses of the UK Household Longitudinal Study

Abstract: BackgroundThere are concerns that COVID-19 mitigation measures, including the ‘lockdown’, may have unintended health consequences. We examined trends in mental health and health behaviours in the UK before and during the initial phase of the COVID-19 lockdown and differences across population subgroups.MethodsRepeated cross-sectional and longitudinal analysis of the UK Household Longitudinal Study, including representative samples of over 27,000 adults (aged 18+) interviewed in four survey waves between 2015 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
450
10
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 457 publications
(540 citation statements)
references
References 31 publications
69
450
10
11
Order By: Relevance
“…How can we, given the outcomes of several studies showing an increase in mental health problems [9][10][11][12][13][14][15][16][17], understand the contradicting results of the present study? In addition, in our previous study [18] we observed a significant increase in emotional loneliness which is considered a risk factor for future mental health problems [33,34].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 65%
See 1 more Smart Citation
“…How can we, given the outcomes of several studies showing an increase in mental health problems [9][10][11][12][13][14][15][16][17], understand the contradicting results of the present study? In addition, in our previous study [18] we observed a significant increase in emotional loneliness which is considered a risk factor for future mental health problems [33,34].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 65%
“…The study by Proto and Quintana-Domeque [10] showed similar findings up to April 2020 but focused especially on ethnicity and gender. Niedzwiedz et al [11] also examined smoking, drinking and the separate items of the GHQ-12 up to April 2020. Their results showed that smoking declined (Relative Risk (RR)=0.9) and that the proportion of people drinking four or more times per week increased (RR=1.4) as did binge drinking (RR=1.5).…”
Section: Results Prospective Studies Ukmentioning
confidence: 99%
“…Resilient coping was assessed using the Brief Resilient Coping Scale (42) with a score range of 4-20. Resilient coping was defined as low (score of 4-13), medium (score of 14-16), or high (score of [17][18][19][20]. Compliance with COVID-19 lockdown measures was examined using a series of 4-point Likert scales: 1 (always), 2 (sometimes), 3 (seldom), and 4 (never).…”
Section: Measures and Instrumentsmentioning
confidence: 99%
“…More recently, longitudinal studies examining the impact of COVID-19 on mental health have started to emerge ( Table 1, Supplementary Figure 1). These studies most commonly assessed general mental distress at the time (26)(27)(28)(29)(30) or addressed specific symptoms of mental distress by comparing COVID-19 with pre-COVID-19 data obtained largely from national survey-based probability samples (17,(19)(20)(21)31). Collectively, these studies showed significantly increased mental distress in response to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Quarantine measures such as those imposed during the pandemic can have a negative psychological impact(Brooks et al, 2020) and concerns have been raised about the specific impact of COVID-19 lockdown measures on the mental health of the general population(Gunnell et al, 2020) as well as particular vulnerable groups including care recipients and their carers. (Holmes et al, 2020) Emerging evidence demonstrates that population mental health worsened in the early stages of lockdown(Niedzwiedz et al, 2020) although this may have reversed in the longer-term. (Chandola, Kumari, Booker & Benzeval, 2020) However, a number of carer-specific surveys have reported significant worsening of mental health both in the short(Carers UK, 2020a; Pavopoulou, Wood & Papadopoulos, 2020; Reaching Families, 2020) and longer term,(Carers UK, 2020b) although they do not make direct comparisons with the experiences of non-carers.…”
Section: Introductionmentioning
confidence: 99%